HUBUNGAN BEBAN KERJA PERAWAT DENGAN SIKAP PENDOKUMENTASIAN ASUHAN KEPERAWATAN DI RUMAH SAKIT PKU MUHAMMADIYAH SURAKARTA - Suyanti, Suyanti; , Endang Zulaicha S, S. Kp., M. (2016)
Documentation of nursing care attitude is an attitude held by nurses in carrying out the tasks of nursing care documentation, which is possible to have a relationship with the workload. The purpose of this study was: (1) to determine the workload of nurses at the Hospital of PKU Muhammadiyah Surakarta. (2) to determine the behavior of nursing care documentation in PKU Muhammadiyah Hospital in Surakarta. (3) to analyze the relationship workload of nurses with the attitude of nursing care at the Hospital of PKU Muhammadiyah Surakarta. The study was conducted at the Hospital of PKU Muhammadiyah Surakarta. The population in this study are all nurses PKU Muhammadiyah Hospital in Solo as many as 226 people, divided into 12 spaces. The sample in this study was set at 45 respondents (20%). Techniques propotionate side by using stratified random sampling technique. Data collection techniques using questionnaires. Data analysis techniques using crosstab chi square analysis. Results of the study workload of nurses mostly with medium category by 32 (71%). The attitude of nursing care documentation, showing mostly the medium category by 31 nurses (68.89%). There is a relationship between workload against the attitude of nursing care documentation at the Hospital of PKU Muhammadiyah Surakarta as evidenced by the value of the Pearson chi-square (χ2-count) of 12.011 with a probability value of 0.017 calculated χ2 value (12.011)> χ2 table (9.49), The study concluded that there is a relationship between workload against the attitude of nursing care documentation in PKU Muhammadiyah Hospital in Surakarta.